Algemene tugmaatreëls in primêre skole van die Transvaalse Onderwysdepartement1 - Oosthuizen, I. J. (Koers, 1993)
Amidst a worldwide trend of undisciplined behaviour, discipline in the classroom is regarded as crucial for pupils to learn effectively. In this article empirical data are analysed to determine the reasons for undisciplined behaviour among pupils and what point o f view motivates teachers when applying general disciplinary methods. Apart from this, the article determines, by means o f an analysis o f empirical research, which o f the general methods o f control are favoured by teachers in the maintaining o f order in the educative environment. It also analyses the pupil's responses to the administration o f general methods o f control at school.